2020
DOI: 10.1037/ppm0000226
|View full text |Cite
|
Sign up to set email alerts
|

You’re not anonymous online: The development and validation of a new cyberbullying intervention curriculum.

Abstract: Cyberbullying is a pervasive phenomenon that leads to a variety of damaging psychological consequences for its victims. Myriad theoretical frameworks, including the Barlett Gentile Cyberbullying Model, have emphasized the role of online anonymity perceptions in predicting cyberbullying behavior.In the present study, we implemented a theory-based video intervention program designed to challenge college students' anonymity perceptions to reduce subsequent cyberbullying. Then, we examined their cyberbullying beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
0
16
0
2
Order By: Relevance
“…First, as already discussed, there is preliminary evidence that BGCM tenets apply to youth. Second, research has shown that an intervention that teaches individuals that they are not as anonymous as they believe can reduce anonymity perceptions, which causes changes in cyberbullying perpetration 2 months later in emerging adults (Barlett et al, 2020 ). Therefore, an intervention that incorporates BGCM postulates should help to reduce cyberbullying perpetration through a reduction in either anonymity perceptions, BIMOB, and/or cyberbullying attitudes.…”
Section: Cyberbullying Theory and Interventionsmentioning
confidence: 99%
“…First, as already discussed, there is preliminary evidence that BGCM tenets apply to youth. Second, research has shown that an intervention that teaches individuals that they are not as anonymous as they believe can reduce anonymity perceptions, which causes changes in cyberbullying perpetration 2 months later in emerging adults (Barlett et al, 2020 ). Therefore, an intervention that incorporates BGCM postulates should help to reduce cyberbullying perpetration through a reduction in either anonymity perceptions, BIMOB, and/or cyberbullying attitudes.…”
Section: Cyberbullying Theory and Interventionsmentioning
confidence: 99%
“…Cyber sexual IPA victimization may have particularly long-lasting consequences as messages and photographs can be saved and posted to larger audiences on the internet. To target cyber IPA specifically, programs could adapt existing cyberbullying interventions, which have been found to reduce rates of online perpetration and victimization by addressing inaccurate perceptions of anonymity, online disinhibition, and building virtual communication skills (Barlett et al, 2019;Gaffney et al, 2019;Palladino et al, 2016). Because of the co-occurrence between cyber and in-person IPA, these programs may be most effective when incorporated as part of in-person violence prevention to reduce risk for cyber and in-person IPA simultaneously.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Cyberbullying can be defined as a form of intentional harassment that is directed at a particular person, carried out through electronic and digital means and produced by an imbalance of power associated with greater development of technical skills when using the internet (Smith et al, 2013;Olweus and Limber, 2018). Additionally, anonymity is considered a significant risk factor in this phenomenon (Barlett et al, 2016(Barlett et al, , 2020. On the other hand, cyberbullying is considered a social phenomenon that can negatively affect victims, aggressors, and bully/victims, significantly increasing the risk of suicide (DeSmet et al, 2014(DeSmet et al, , 2019Hellfeldt et al, 2020;Kim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%